2016
DOI: 10.3727/096504016x14549667334007
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lncRNA and Its Role in Cancer Metastasis

Abstract: Metastasis is the primary cause of cancer-related death all over the world. Metastasis is a process by which cancer spreads from the place at which it first arose to distant locations in the body. It is well known that several steps are necessary for this process, including cancer cell epithelial-mesenchymal transition (EMT), cell migration, resistance to anoikis, and angiogenesis. Therefore, investigating the molecular mechanism of regulating cancer metastasis progress may provide helpful insights in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
164
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(164 citation statements)
references
References 123 publications
0
164
0
Order By: Relevance
“…Increasing reports of aberrant expression of lncRNAs across numerous cancer types suggested that some lncRNAs could promote the formation and development of tumors 1618. With regard to these latter effects, expression levels of certain lncRNAs have been shown to be associated with the recurrence, metastasis, and prognosis of various cancers (HCC, gastric carcinoma, and breast carcinoma) 1921.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing reports of aberrant expression of lncRNAs across numerous cancer types suggested that some lncRNAs could promote the formation and development of tumors 1618. With regard to these latter effects, expression levels of certain lncRNAs have been shown to be associated with the recurrence, metastasis, and prognosis of various cancers (HCC, gastric carcinoma, and breast carcinoma) 1921.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a small proportion of lncRNAs have been demonstrated to be biologically functional (20). Among the functional lncRNAs, the majority have been implicated in malignant tumors (10,21). The lncRNA, EGOT, was initially thought to be involved in eosinophil development and expressed in mature eosinophils (16); it was subsequently demonstrated that EGOT locus is highly structured, containing several evolutionary conserved regions, and thermodynamic stable secondary structures (22).…”
Section: Discussionmentioning
confidence: 99%
“…With continuous advances in research approaches, research focused on lncRNAs has recently undergone a rapid expansion. LncRNAs are closely associated with tumor development (9,10) and particularly, have been implicated in glioma progression (11). For example, the lncRNA, MALAT1, has been demonstrated to have crucial roles in the cell proliferation, metastasis and apoptosis processes in glioma (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have been recently reported to play an important role in various malignancies, including CRC. [18][19][20] However, global lncRNA expression profile in CRC is not fully clear, and more evidences are needed to uncover the role of lncRNAs in CRC. In this study, we performed microarray analysis in CRC tissue and paired normal tissue to investigate the global expression profile of lncRNA and look for lncRNAs that have potential to be a CRC diagnostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%